Merkel Cell Carcinoma of the External Ear: Population-Based Analysis and Survival Outcomes - Alves Andre S; Scampa Matteo; Martineau Jerome; Giordano Salvatore; Kalbermatten Daniel F; Oranges Carlo M (MDPI, 2025)
(1) Background: Due to its highly aggressive behavior, the ability to identify and manage Merkel Cell Carcinoma (MCC) with a full understanding of its characteristics is essential. Because the external ear is an exposed area, resection can have dramatic consequences on patient's self-image, which is why it is fundamental to detect MCC, typically found on UV-exposed regions such as the ears, at an early stage.
(2) Methods: The Surveillance, Epidemiology, and End Results (SEER) database was searched for all external ear MCC between 2000 and 2019. A descriptive analysis based on frequencies was made to describe the demography of pathophysiologic features linked to MCC. Overall survival (OS) was studied and compared between variables with a log rank test. A multivariable Cox regression analysis was then computed to identify independent prognostic factors.
(3) Results: A total of 210 patients (160 men) were identified with a median age of 80 years. The median OS was 47 months. Factors associated with lower OS included an age of over 80 years, the male gender, a tumor size of >5 cm, and metastatic disease. Gross (<1 cm) and wide (>1 cm) surgery excision margins were the surgery types with the best OS.
(4) Conclusions: MCC of the external ear is diagnosed mostly in old men. Among the 182 patients who received a surgical procedure, gross and wide excision without radiotherapy were associated with the best OS.